The vascular epiphytic flora of the State of Hidalgo, Mexico: diversity and distribution - Ceja-Romero, Jacqueline; Mendoza-Ruiz, Aniceto; López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo; Pérez-García, Blanca; García-Cruz, Javier (Instituto de Ecología, A.C., 2010)
Based on the recollection of botanical specimens in different regions of the state of Hidalgo and the study of herbarium material deposited in several institutional collections, supplemented by a literature review, we obtained records of 17 families (nine of them belonging to Pteridophytes and the rest to Angiosperms), 64 genera and 163 species. We also provide data about the municipal distribution of taxa and an analysis of their representation by vegetation type and altitudinal range. We report from Hidalgo, for the first time the following taxa: Tillandsia filifolia Schltdl. & Cham., T. heterophylla E. Morren, Pleurothallis sp.1 and Pleurothallis sp. 2. Only Laelia gouldiana Rchb. f., Dignathe pygmaeum Lindl., and one undescribed species of the genus Goodyera, are endemic to the state.